Analysis of Malaysia's role in the South China Sea dispute between China and the United States - Siti Khadijah Zainal Abidin (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2021)
This research looks at Malaysia’s relations in term of the security, political and economy with the United States and China in relation to the South China Sea (SCS) dispute. By analysing the hedging factors that influence Malaysia’s response, the study is guided by a theoretical framework consisting of constructive theory. The study used qualitative and interpretative analysis method. It collects data from both primary and secondary sources. According to the analysis of the factors, Malaysia decides to use pragmatic resolution through the United Nations and ASEAN in discussing the dispute. Malaysia has used the UN’s role to coordinate with the US, while Malaysia has used the ASEAN community role to discuss with China. Findings of this study has found that, Malaysia’s South China Sea policy is a rationally calculated and pragmatic foreign policy that employs a combination of military cooperation, legal means, and hedging diplomacy between China and the United States. Finally, based on the discussion in chapter four, this study provides several important recommendations.